Managing sensory expectations concerning products and brands: Capitalizing on the potential of sound and shape symbolism - Spence, C (2012)
In this article, the evidence demonstrating the existence of a variety of robust crossmodal correspondences between both sounds (phonetic speech sounds, tones, and other parameters of musical expression) and shapes, and the sensory attributes (specifically the taste, flavor, aroma, and oral-somatosensory attributes) of various foods and beverages is reviewed. The available research now clearly suggests that marketers can enhance their consumers' product experiences by ensuring that the sound symbolism of the brand name, as well as any shape symbolism of/on the labeling, and even the very shape of the packaging itself, sets up the right (i.e., congruent) product-related sensory expectations in the mind of the consumer. In this review, the rapidly-growing literature on the topic of sound and shape symbolism is critically evaluated. Potential caveats, limitations, and problems of interpretation with previous studies are highlighted. The question of whether this approach to sensory marketing should be considered as implicit (or functionally subconscious) is also addressed. Finally, some of the relative strengths and weaknesses of this approach to modulating a consumer's product-related expectations (relative to various other approaches) are considered. © 2011 Society for Consumer Psychology.